Quality intrapartum care and associated factors in East Africa: multilevel analysis of recent demographic and health survey - Gebrehana, Alemayehu Kasu; Asnake, Angwach Abrham; Seifu, Beminate Lemma; Fente, Bezawit Melak; Melkam, Mamaru; Bezie, Meklit Melaku; Asmare, Zufan Alamrie; Tsega, Sintayehu Simie; Negussie, Yohannes Mekuria; Asebe, Hiwot Altaye (Frontiers in Global Women's Health, 2024)
BackgroundThe time during labor and delivery is crucial for the survival of both women and their infants, as complications that occur during this period can significantly increase the risk of morbidity and mortality. In developing nations, women of reproductive age and their infants are still at risk of morbidity and death from complications associated with pregnancy and childbirth. Morbidity and death from complications of pregnancy and childbirth can be prevented through the utilization of quality care during labor and delivery. However, there is limited evidence on the magnitude and factors associated with quality intrapartum care in East Africa. Therefore, this study assessed the magnitude and associated factors of quality intrapartum care among women in East Africa.MethodsIn this study, we used the most recent Demographic and Health Survey (DHS) dataset from 2015 to 2023, covering 11 East African countries. STATA version 18 software was used for data analysis. Multi-level modeling was applied due to the hierarchical or nested structure of DHS data. Variables with a p-value of less than 0.25 in the bivariate multi-level logistic regression model were included in the multivariable multi-level logistic regression analysis. Variables with p-values less than 0.05 were considered significant factors associated with receiving quality intrapartum care.ResultsThe prevalence of receiving quality intrapartum care in East Africa was 56.38% [95% confidence interval (CI): 56.03, 56.7]. Women with primary education [Adjusted Odds Ratio (AOR) = 1.39, 95% CI: 1.33, 1.46], secondary education (AOR = 1.62, 95% CI: 1.53, 1.62), and higher education (AOR = 1.46, 95% CI: 1.33, 1.60), those in the middle (AOR = 1.28, 95% CI: 1.23, 1.34) and rich (AOR = 1.36, 95% CI: 1.31, 1.43) wealth index categories, women with one (AOR = 1.17, 95% CI: 1.09, 1.25) or 2–4 (AOR = 1.22, 95% CI: 1.16, 1.28) living children, those who perceived the distance from the health facility as not a big problem (AOR = 1.28, 95% CI: 1.24, 1.33), and women living in Rwanda (AOR = 1.30, 95% CI: 1.19, 1.41) had higher odds of receiving quality intrapartum care. Residing in rural areas (AOR = 0.82, 95% CI: 0.78, 0.86), and being from Ethiopia, Kenya, Madagascar, Malawi, Mozambique, Tanzania, Uganda, Zambia, or Zimbabwe, were factors negatively associated with receiving quality intrapartum care.Conclusion and recommendationsNearly half of the women in East African countries did not receive quality intrapartum care. Both individual and community-level variables were significantly associated with receiving quality intrapartum care in East Africa. Improving the quality of intrapartum care requires enhancing women's education, addressing socioeconomic challenges, and increasing access to health facilities through targeted interventions.